Effect of Bion and Amistar in inducing resistance against Cercospora leaf spot of banana: Inducing resistance in banana production (Journal of the Bangladesh Agricultural University, 2018)
Bion (benzothiadiazole) and Amistar (azoxystrobin) were applied for controlling Cercospora leaf spot of banana variety Amrita Sagarin at the field laboratory, Department of Plant Pathology, Bangladesh Agricultural University (BAU), Mymensingh by applying different treatments viz. dipping bottom of sucker for 6 hrs. in Bion (0.005%) before planting, dipping bottom of sucker for 6 hrs. in Bion (0.01%) before planting, spraying of Bion @ 0.005% once on leaves after 80 days of planting, spraying of Bion @ 0.01% once on leaves after 80 days of planting, spraying of Amistar @ 0.05% once on leaves after 80 days of planting, spraying of Amistar @ 0.05% only on leaves after 80 and 140 days of planting, spraying of Bion @ 0.005%) once on leaves and pseudostem after 80 days of planting, spraying of Bion @ 0.01% once on leaves and pseudostem after 80 days of planting and control (without chemical). From these above treatments it is revealed that dipping of bottom of banana sucker for 6 hrs. in Bion either @ 0.005% or 0.01% significantly reduced plant height, while Bion and Amistar did not exert any effect on number of leaf/ plant. Bion @ 0.005% and 0.01% (dipping of bottom of sucker before planting), Bion @ 0.01% (on leaves, 1 spray) and 0.01% (on leaves and pseudostem, 1 spray) and Amistar @ 0.05% (on leaves, 2 spray) showed significant effect in reducing number of diseased leaf/ plant, number of diseased spot/ plant, percent leaf area (cm2) diseased/ plant, mean spot size (mm2)/ plant of banana var. Amrita sagar.J.Bangladesh Agril. Univ. 16(3): 380–385, December 2018